Influence of anti-tobacco advertisements on the attitude of slum dwellers about use of tobacco: a cross-sectional study from Mandya city - Rudresh, Harish B.; Gowda, Sudhir (International Journal Of Community Medicine And Public Health, 2019)
Background: As per the Cigarette and Other Tobacco Products Act (COTPA) rules, the anti-tobacco health spots and disclaimers are being provided by the Ministry of Health and Family Welfare, India. These advertisements are aimed at creating awareness about the ill effects of tobacco use. Mass media anti-tobacco advertising campaigns play an important role as part of a comprehensive tobacco control program and are associated with increase in smoking cessation and declines in adult tobacco use prevalence. Methods: This cross-sectional study was conducted to assess the influence of anti-tobacco advertisements among slum dwellers of Mandya city. A self-structured, close-ended questionnaire was used to interview 700 slum dwellers. The questionnaire consisted of sociodemographic data, tobacco usage status, questions related to awareness about anti-tobacco advertisements, and influence of anti-tobacco advertisements on attitude toward tobacco use. Frequency distributions and percentages were examined for each item and Chi-square test was used. Results: Out of 700 participants 54.5% were males and 45.5% were females. Nearly 87.7% of males and 70.2% of females had noticed the statutory warning which is shown during tobacco products’ usage on television/movies. Almost 66.4% of males and 68.0% of females had a positive change in attitude toward tobacco use due to influence of anti-tobacco advertisements. Conclusions: There is awareness against use of tobacco and this awareness should be used to motivate them to quit tobacco as well as to stop them from initiating tobacco use.